PENGARUH MERCHANDISE EVALUATION, PERCEIVED CROWDING, DAN STORE ATMOSPHERE EVALUATION TERHADAP STORE PATRONAGE INTENTIONS KONSUMEN SUPERMARKET DI MALL SURABAYA - Kevin Kurniawan (Jurnal Strategi Pemasaran, 2019)
This study analyzed the influence of Merchandise Evaluation, Perceived Crowding dan Store Atmosphere Evaluation on Store Patronage Intentions. This research is conclusive and classified in the type of causal research using a quantitative approach. Data was collected through an online survey using a questionnaire instrument with a response that could be used from 104 supermarket customer respondents at a mall located in Surabaya. Data is processed using the structural model equation approach with Partial Least Square Technique. The results of this study indicate that (1) Merchandise Evaluation has a significant effect on Store Atmosphere Evaluation; (2) The perceived crowding has a significant effect on Store Atmosphere Evaluation; (3) Store Atmosphere Evaluation has a significant influence on Store Patronage Intentions.